Investigating the Relationship Between Fin and Blue Whale Locations, Zooplankton Concentrations and Hydrothermal Venting on the Juan de Fuca Ridge - Wilcock, William S.; Thomson, Richard E. (2008)
We are investigating the potential correlation between whale tracks, enhanced zooplankton concentrations and hydrothermal vents above the Juan de Fuca Ridge with the long-term goal of understanding such correlations in terms of the influences of globally distributed hydrothermal plumes on the trophic ecology of the deep ocean. We are conducting a retrospective study using existing seismic and bio-acoustical data sets from the Juan de Fuca Ridge with the following four objectives: 1. Implementing an automatic algorithm to track fin and blue whales using data from a small-scale seafloor seismic network. 2. Tracking vocalizing fin and blue whales above the Endeavour segment over a 3-year interval from 2003-2006 in order to determine whether they are preferentially found above the hydrothermal vent fields where the bio-acoustical data show that the zooplankton concentrations are higher at all depths. 3. Analyzing a total of 60 net tow samples from the Endeavour Segment from 1995 and 1996 and combining these with 119 previously analyzed net-tow samples from 1991-1994 to refine our understanding of the variations of zooplankton concentrations at different depths with distance from the vent fields. Using the simultaneous acoustic backscatter and net tow data to calibrate the acoustic observations so that we can make use extensive acoustic Doppler current profiler (ADCP) data sets that already exist for the region (as well as ADCP data that may be collected in the future) to estimate zooplankton concentrations. The central portion of the Endeavour Segment of the Juan de Fuca Ridge (129 deg. W, 48 deg. N) hosts several large hydrothermal vent fields and has been extensively studied by marine geoscientists for over two decades. It is presently one of three sites at which NSF's RIDGE2000 program is conducting Integrated Studies.